SANKSI BAGI PENISTAAN (PENODAAN) TERHADAP AGAMA DALAM PERSPEKTIF HUKUM PIDANA INDONESIA DAN HUKUM PIDANA ISLAM - Fitri Wahyuni (Fakultas Hukum Universitas Islam Indragiri, 2017)
Indonesia is not a religious state, nor a secular state because religion can not be separated from state affairs. Recognition of the existence of the state of religion in Indonesia is realized in the form of official recognition of certain religious institutions in the country as well as the adoption of values ​​and religious norms in the national system. However, the current phenomenon occurs sacrilege (desecration) to religion that is a violation of applicable law in Indonesia. According to the criminal law of defamation positive (desecration) religion can be imposed sanctions in the form of imprisonment. However, sanctions imposed for perpetrators of the desecration (penistaa) religion in the positive criminal law in Indonesia is relatively lower, it can be found on the article 156 of the Criminal Code which only impose sanctions in the form of imprisonment to five years so that these penalties do not give a deterrent to perpetrators of sacrilege religion. Whilst Islamic criminal law sanctions against perpetrators of sacrilege (desecration) religion with more severe sanctions by the death penalty. It is based on the opinion of the jurists who established that religious treason or blasphemy included in offenses (jarimah hudud) and the witnesses in the form of the death penalty. The imposition of severe sanctions for defamation (desecration) religion in Islamic criminal law aimed at protecting religion in order to avoid abuse (desecration) religion done by humans who make mischief on earth.